PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) UNTUK MENGATASI KECEMASAN MATEMATIKA SISWA KELAS V SD PADA MATERI KELILING BANGUN DATAR - Yusup Nurdiansah; Rina Heryani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is based on the high level of mathematics anxiety experienced by elementary school students, especially in the material on the perimeter of plane figures. This anxiety impacts students' low participation, self-confidence, and logical thinking skills. This condition is exacerbated by the teacher-centered and monotonous learning method. This research aims to reduce students' mathematics anxiety through the implementation of the Teams Games Tournament (TGT) cooperative learning model, which combines elements of cooperation, games, and healthy competition in learning activities. The method used is the Classroom Action Research (CAR) model of Kemmis and McTaggart with four stages, namely planning, implementation of actions, observation, and reflection. The research subjects involved 24 fifth-grade students of Sayang Jatinangor State Elementary School in the odd semester of the 2025/2026 academic year. Data were collected using a mathematics anxiety questionnaire, observation sheets, and interviews, then analyzed descriptively quantitatively and qualitatively. The results showed that the implementation of the TGT model reduced the average mathematics anxiety score from 70.4 (high category) to 39.5 (very low) after three cycles. Furthermore, student engagement increased from 45% to 95%, and group collaboration reached 96%. Learning became more enjoyable, communicative, and stress-free. Thus, the TGT model is effective in reducing math anxiety and increasing students' self-confidence and social interaction.